Determination of Iodate in Food, Environmental, and Biological Samples after Solid-Phase Extraction with Ni-Al-Zr Ternary Layered Double Hydroxide as a Nanosorbent - Hossein Abdolmohammad-Zadeh; Keyvan Tavarid; Zeynab Talleb (The Scientific World Journal)
Nanostructured nickel-aluminum-zirconium ternary layered double hydroxide was successfully applied as a solid-phase extraction sorbent for the separation and pre-concentration of trace levels of iodate in food, environmental and biological samples. An indirect method was used for monitoring of the extracted iodate ions. The method is based on the reaction of the iodate with iodide in acidic solution to produce iodine, which can be spectrophotometrically monitored at 352 nm. The absorbance is directly proportional to the concentration of iodate in the sample. The effect of several parameters such as pH, sample flow rate, amount of nanosorbent, elution conditions, sample volume, and coexisting ions on the recovery was investigated. In the optimum experimental conditions, the limit of detection (3s) and enrichment factor were 0.12 μg mL−1 and 20, respectively. The calibration graph using the preconcentration system was linear in the range of 0.2–2.8 μg mL−1 with a correlation coefficient of 0.998. In order to validate the presented method, a certified reference material, NIST SRM 1549, was also analyzed.